Creating a Vision for Your School : Moving from Purpose to Practice. - Bainbridge, Sarah (Lucky Duck Books., 2007)
Approaching school development as a training project for all staff, this book will help schools to work towards collectively selected goals. It also shows how to involve parents, governors and, most importantly, the pupils. The book describes a school development process consisting of two inset days followed by a series of staff meetings. A set of activities links the events and requires active participation by all staff, working with pupils to complete the tasks. Copiable resources on a CD-ROM are included which will help readers to reach an outcome suited to their own establishment and cultu.